The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41386-022-01360-y
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and neurotrophic effects of GABAA receptor positive allosteric modulation in a mouse model of chronic stress

Abstract: Chronic stress is a risk factor for Major depressive disorder (MDD), and in rodents, it recapitulates human behavioral, cellular and molecular changes. In MDD and after chronic stress, neuronal dysfunctions and deficits in GABAergic signaling are observed and responsible for symptom severity. GABA signals predominantly through GABAA receptors (GABAA-R) composed of various subunit types that relate to downstream outcomes. Activity at α2-GABAA-Rs contributes to anxiolytic properties, α5-GABAA-Rs to cognitive fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 98 publications
5
25
0
Order By: Relevance
“…At 5 months of age, we found GL-II-73 had a dose dependent effect in remedying the cognitive deficit. This is consistent with our previous work showing dose dependent benefits of 10mg/kg over 5mg/kg in the unpredictable chronic mild stress model and aging model 24,29 . Here, the 5 month chronic study also showed spatial working memory deficits reversed by GL-II-73.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…At 5 months of age, we found GL-II-73 had a dose dependent effect in remedying the cognitive deficit. This is consistent with our previous work showing dose dependent benefits of 10mg/kg over 5mg/kg in the unpredictable chronic mild stress model and aging model 24,29 . Here, the 5 month chronic study also showed spatial working memory deficits reversed by GL-II-73.…”
Section: Discussionsupporting
confidence: 93%
“…This study was designed to investigate the impact of modulation of α5-GABAA receptors at early and late amyloid deposition to determine functional, morphological and histological effects related to cognition and pathology. This work was driven by observations that SST interneurons and the GABAergic system is affected in AD, and that selective α5 GABA-A-R modulation has pro-cognitive effects in models of stress and aging which are also well documented risk factors for AD 24,29 . In the 5XFAD model of amyloid load, we tested acute and chronic GL-II-73 at 2 months of age and 5 months of age on spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from early studies indeed indicated that BDZ modulation of α1GABAARs is required for the sedative effects ( 14 ), while BDZ modulation of α2GABAARs is required for the anxiolytic-like effects of BDZs ( 15 ). Continued work in this area not only confirmed and further expanded the association of specific behavioral effects with specific GABAAR subtypes ( 16 25 ), but uncovered new, previously unappreciated indications for subtype-selective GABAAR modulation ( 26 30 ).…”
Section: Introductionmentioning
confidence: 90%
“…The literature consistently shows that suppression of adult hippocampal neurogenesis caused by stress ( Besnard and Sahay, 2016 ; Drew and Huckleberry, 2017 ; Huckleberry et al, 2018 ) might contribute to a maladaptive emotional and stress-coping strategy. Several lines of evidence have indicated that the prefrontal cortex (PFC) is particularly vulnerable to stress, where stress induces volumetric ( de Lange et al, 2008 ; McEwen et al, 2016 ; Misquitta et al, 2021 ), cytoarchitectural ( Misquitta et al, 2021 ), and morphological changes, including the reduction of dendrite length, branching, and spine density ( McEwen, 1997 ; McEwen and Magarinos, 1997 ; Radley et al, 2006 ; Arnsten, 2009 ; Kang et al, 2012 ; Arnsten et al, 2015 ; Qiao et al, 2016 ; Moreno et al, 2017 ; Banasr et al, 2021 ; Bernardo et al, 2022 ). In addition, altered PFC neuronal activity is associated with social defeat-induced depression- and anxiety-like behavior in mice, and learning and memory impairments ( Sullivan and Gratton, 2002 ; Lupien et al, 2009 ; Felix-Ortiz et al, 2016 ; Burgos-Robles et al, 2017 ; Planchez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%